2013
DOI: 10.4269/ajtmh.13-0307
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Confirmed Cholera and Rotavirus among Patients with Acute Diarrhea in Four Hospitals in Haiti, 2012–2013

Abstract: An outbreak of cholera began in Haiti in October of 2010. To understand the progression of epidemic cholera in Haiti, in April of 2012, we initiated laboratory-enhanced surveillance for diarrheal disease in four Haitian hospitals in three departments. At each site, we sampled up to 10 hospitalized patients each week with acute watery diarrhea. We tested 1,616 specimens collected from April 2, 2012 to March 28, 2013; 1,030 (63.7%) specimens yielded Vibrio cholerae, 13 (0.8%) specimens yielded Shigella, 6 (0.4%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 18 publications
(14 reference statements)
1
44
0
Order By: Relevance
“…The typical peak season for RVA disease in tropical countries is during the dry season (which is typically December to March in Haiti). 12 During a full year of RVA sentinel surveillance in Haiti, 9 among patients with acute watery diarrhea, RVA was found in 13.5% of specimens from children 5 years, 3.9% from children 5-18 years, and 1% from persons 18 years of age.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The typical peak season for RVA disease in tropical countries is during the dry season (which is typically December to March in Haiti). 12 During a full year of RVA sentinel surveillance in Haiti, 9 among patients with acute watery diarrhea, RVA was found in 13.5% of specimens from children 5 years, 3.9% from children 5-18 years, and 1% from persons 18 years of age.…”
mentioning
confidence: 99%
“…Specimens received at the NPHL were tested for RVA using Premier™ Rotaclone (Meridian Diagnostics, Cincinnati, OH) enzyme immunoassay (EIA). 9 Of the 392 specimens received at NPHL in April-June 2012, 200 were available for further analysis and shipped to the Rotavirus Surveillance Laboratory, U.S. Centers for Disease Control and Prevention (CDC) for further characterization. Of the 200 specimens, 38 were known to be from children 5 years of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,12 Recent results from a laboratory-based surveillance system for diarrhea in Haiti showed that, during 2012-2013, rotavirus peaked in the first few months of the calendar year. 7 More years of data collection are needed to better understand the seasonality of diarrheal hospitalizations in Haiti.…”
mentioning
confidence: 99%
“…7 These hospitals were chosen for inclusion in the surveillance system, because they are large facilities and located within a 3-hour drive of the National Public Health Laboratory (LNSP) in Port-au-Prince, making transport of specimens easily manageable. Two hospitals are in Port-au-Prince (one public and one mission hospital), and one hospital is in each of the Artibonite and Southeast Departments (both public hospitals) ( Table 1).…”
mentioning
confidence: 99%